The Influence of Lifestyle, Income, Financial Technology Adoption, and Financial Literacy on Personal Financial Management among Young Workers in Jakarta - Dionosius, Lius; Burhan, Aditya (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study aims to analyze the influence of lifestyle, income, financial technology (fintech) usage, and financial literacy on the financial management of young workers in Jakarta. A quantitative approach was employed involving 455 respondents selected through purposive sampling technique. Data were collected using a Likert-scale questionnaire that had undergone validity and reliability testing, subsequently analyzed through multiple linear regression using SPSS version 25. Prior to hypothesis testing, a series of classical assumption tests were conducted, including normality, heteroscedasticity, and multicollinearity tests, all of which were satisfactorily fulfilled. The results indicate that simultaneously all four variables significantly influence financial management, with an F-value of 166.106 and an R-Square of 59.6%. Partially, lifestyle exerts a significant negative effect, whereas income, fintech usage, and financial literacy each demonstrate a significant positive influence on the financial management of young workers. Financial literacy emerges as the strongest predictor with the highest t-value of 8.270, followed by fintech usage with the largest regression coefficient of 0.729. These findings imply the necessity of a comprehensive, targeted, and sustainable financial empowerment strategy for the urban productive generation in Indonesia.